Pharmacologic therapy with flecainide for asymptomatic Wolff–Parkinson–White syndrome in an infant with severe left ventricular dyssynchrony. (31st May 2018) - Suzuki, Sayo; Hokosaki, Tatsunori; Iwamoto, Mari
Abstract: Some asymptomatic patients with Wolff–Parkinson–White syndrome have severe left ventricular dyssynchrony and dysfunction. We describe a patient who was given a diagnosis of Wolff–Parkinson–White syndrome in infancy and had a complete response to pharmacologic therapy with flecainide. Our findings suggest that flecainide is a suitable resynchronisation therapy for such infants.